Differential Expression of PLAG1 in Apocrine and Eccrine Cutaneous Mixed Tumors: Evidence for Distinct Molecular Pathogenesis. (April 2020) - Russell-Goldman, Eleanor; Dubuc, Adrian; Hanna, John
Abstract : Abstract: Cutaneous mixed tumors, also known as chondroid syringomas, are benign adnexal neoplasms that share histomorphologic features with pleomorphic adenomas of the salivary gland. Recent work suggests that the similarity between these 2 tumor types extends to the molecular level because both harbor identical chromosomal rearrangements involving the PLAG1 gene. The resulting nuclear PLAG1 overexpression can be detected by immunohistochemistry and has become a useful diagnostic adjunct for both tumor types. In the skin, however, there are 2 morphologically distinct types of mixed tumor, which have been referred to as apocrine-type cutaneous mixed tumor (AMT) and eccrine-type cutaneous mixed tumor (EMT). Previous studies of PLAG1 expression in cutaneous mixed tumor did not distinguish between these types. Here, we evaluated PLAG1 expression by immunohistochemistry in a cohort of 25 cutaneous mixed tumors stratified by type. PLAG1 was overexpressed in the majority of AMT cases (14 of 16) but in none of the EMT cases (0 of 9). A second gene, HMGA2, known to be upregulated in a subset of salivary gland pleomorphic adenomas, was overexpressed in only 1 case of AMT (1 of 16) and in none of the cases of EMT (0 of 9). Our results indicate that apocrine- and eccrine-type mixed tumors are associated with different pathways of molecular pathogenesis and suggest that the emerging relationship between skin and salivary gland mixed tumors is likely limited to those of apocrine type.